EFFECTS OF REPRODUCTIVE CROPS ON SOIL SIZE WEIGHT AND POOR PERFORMANCE IN VEGETABLE-GRAIN CIRCULATION SYSTEM - Khalikov Bahodir Melikovich , Rasulova Feruzaxon G'ofirovna , Karimova Marxabokhon Abdullaevna , Bostonova Surayyo Solievna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
For the first time in the conditions of irrigated light gray soils of Andijan region in short-crop vegetable-grain and vegetable-cotton (1: 1) crop rotation systems were identified optimal past vegetable and secondary crop varieties that provide high and high yields of winter wheat and cotton and increase soil fertility.